Testicular adrenal rest cells in congenital adrenal hyperplasia - Adnan Haider, MD (Elsevier, 2021)
Abstract: We present a case of untreated Congenital adrenal hyperplasia presenting with bilateral giant Adrenal myelolipoma and Testicular adrenal rest cells. Methods: We discuss clinical presentation diagnostic evaluation and subsequent management and follow up of CAH with TART's. Results: Our patient was not adherent to Glucorticoid and mineralocorticoid treatments between age 18 to 47 and presented with back pain most likely resulting from Bilateral giant adrenal myelolipoma. Interestingly he did not require any stress steroids during this time. His adrenal myelolipoma progressively increased in size. Comparison CT is available from 2004 to 2020. Testicular adrenal rest cells and possibly infertility also resulted from uncontrolled CAH for a long period of time. Conclusion: This case demonstrates the significance of CAH treatment compliance and highlights sequela and management of untreated CAH.